Westernization and Colonization of the Mind in Chinua Achebe’s “Dead Men’s Path” - Maria Regina Anna Hadi Kusumawardani (IAIN MADURA, 2021)
British occupation in Nigeria has brought several impacts to the native land and also the indigenous people. Westernization and colonization of the mind are two inseparable effects of colonialism. These two issues are oftentimes depicted in literary works focusing on colonialism as their theme. The aim of this study is to analyze the issues of westernization and colonization of the mind raised in Chinua Achebe's